1-Methylcyclopropene Preserves the Quality of Chive (Allium schoenoprasum L.) by Enhancing Its Antioxidant Capacities and Organosulfur Profile during Storage - Xiaomei Dai; Yaping Lu; Yuan Yang; Zhifang Yu (Foods, 2021)
The quality, antioxidant capacities, and organosulfur profile of chives (Allium schoenoprasum L.) treated with 1-methylcyclopropene (1-MCP) during storage were investigated in this study. The 1-MCP treatment (100 μL/L, fumigation 12 h at 20 °C) effectively inhibited tissue respiration and H2O2 production, enhanced the ascorbic acid (ASA) and glutathione (GSH) content, and promoted the activity of antioxidant enzymes (superoxide dismutase SOD, Catalase CAT, and ascorbic peroxidase APX) during the 5-day storage period at 20 °C. The result further showed that the 1-MCP treatment inhibited chlorophyll degradation, alleviated cell membrane damage, and delayed the chive senescence, with the yellowing rate being reduced by 67.8% and 34.5% in the 1-MCP treated chives on days 4 and 5 of storage at 20 °C, respectively. The free amino acid content of the chive was not affected by the 1-MCP treatment at 20 °C. However, the senescence rate of the chive was not reduced by the 1-MCP treatment when stored at 3 °C. The liquid chromatography data further showed that the 1-MCP treatment induced a 15.3% and 13.9% increase in the isoalliin and total S-alk(en)ylcysteine sulfoxides (ACSOs) content of the chive on day 2 at 20 °C, respectively. Furthermore, there was a strong positive correlation between ACSOs content and CAT/APX activity, indicating that ACSOs probably played a key role in enhancing the antioxidant capacities of the chive during storage at 20 °C. Thus the study efficiently demonstrates that 1-methylcyclopropene preserves the quality of chive (Allium schoenoprasum L.) by enhancing its antioxidant capacities and organosulfur profile during storage.